An Earth-mass planet in a time of COVID-19: KMT-2020-BLG-0414Lb - Zang, Weicheng; Han, Cheongho; Kondo, Iona; Yee, Jennifer C.; Lee, Chung-Uk; Gould, Andrew; Mao, Shude; de Almeida, Leandro; Shvartzvald, Yossi; Zhang, Xiangyu; Albrow, Michael D.; Chung, Sun-Ju; et al. (Research in astronomy and astrophysics, 2021)
We report the discovery of KMT-2020-BLG-0414Lb, with a planet-to-host mass ratio q 2 = 0.9–1.2 × 10−5 = 3–4 ⊕ at 1σ, which is the lowest mass-ratio microlensing planet to date. Together with two other recent discoveries (4 ≲ q/q ⊕ ≲ 6), it fills out the previous empty sector at the bottom of the triangular (log s, log q) diagram, where s is the planet-host separation in units of the angular Einstein radius θE. Hence, these discoveries call into question the existence, or at least the strength, of the break in the mass-ratio function that was previously suggested to account for the paucity of very low-q planets. Due to the extreme magnification of the event, A max ∼ 1450 for the underlying single-lens event, its light curve revealed a second companion with q 3 ∼ 0.05 and |log s 3| ∼ 1, i.e., a factor ∼ 10 closer to or farther from the host in projection. The measurements of the microlens parallax π E and the angular Einstein radius θE allow estimates of the host, planet and second companion masses, (M 1, M 2, M 3) ∼ (0.3 M ⊙, 1.0 M ⊕, 17 MJ ), the planet and second companion projected separations, (a ⊥,2, a ⊥,3) ∼ (1.5, 0.15 or 15) au, and system distance D L ∼ 1 kpc. The lens could account for most or all of the blended light (I ∼ 19.3) and so can be studied immediately with high-resolution photometric and spectroscopic observations that can further clarify the nature of the system. The planet was found as part of a new program of high-cadence follow-up observations of high-magnification events. The detection of this planet, despite the considerable difficulties imposed by COVID-19 (two KMT sites and OGLE were shut down), illustrates the potential utility of this program.